Various Forms of Joy in Lithuanian Textbooks from the Middle of the 19th – Beginning of the 20th Century - Bleizgienė, Ramunė (Tautosakos darbai, 2020)
The article presents an attempt to elucidate different meanings of joy that existed from the middle of the 19th to the beginning of the 20th century. For that purpose, we examine the following textbooks: the ABC-book published in 1860 by Mikalojus Akelaitis, the primer edited by Liudvika Malinauskaitė and Jonas Šliūpas and published in 1886, and a reader compiled by Jadvyga Juškytė, published in 1905. In accordance with the definition of emotions by Michelle Z. Rosaldo, a generalized reconstruction of the historically shaped notion of personality prevailing during certain historical period and its relationship to the experience of joy is undertaken. This correlation is established as a result of analysis of the textbook texts. The concept of emotional style formulated by Dewight R. Middleton validates the possibility of the textual reconstruction of the notion of joy. The notion of emotional standards elaborated by Peter N. Stearns and Carol Z. Stearns, which is also employed in the article, enables associating various kinds of meaning attributed to joy with the emotional standards or prevailing emotionology, rather than with the definite experience of the people from that time. The notion of joy spotted in the ABC-book by Akelaitis reveals certain balance existing at that time between the daily practical and spiritual spheres of human life. This experience of joy appears as a prolonged state of mind, which lasts for as long as the person is able to work according to the traditional norms and live out the life that follows the teachings of the Church. The daily joy is perceived in this book as a real union between God and man, thus the notion of joy shaped here approaches the meaning of bliss. The notion of human personality presented in the primary by the Šliūpas couple is radically different, resting on the positivist paradigm of thinking. However, although the scientific chapters of this book define the human being as setting individual goals by means of self-reflection and participating in the progress of humanity, the fiction texts included in this publication further elaborate on the traditional notion of joy as gratifying one’s parents. In these narratives, the goals of life set for the kids are linked to bringing joy to their parents: persons rightfully following the norms upheld by their parents and community earn positive evaluation manifesting as joy experienced by their parents. Thus, joy is used as means of establishing the desired values. The reader by Juškytė defines human beings as creatures governed by five senses, and joy appears here as a sensual, spontaneous experience. It is attributed in the reader to certain environment – namely, the spring. This season is believed to activate and develop all the human senses. The delightful experience of human completeness does not separate the person from the world, rather vice versa: deep feeling of the vernal nature subsumes the person into the surrounding world. During the period of national awakening, the latter form of experiencing joy was treated as a feature of the Lithuanian national character.